The Role of Classroom Interaction in Enhancing The EFL Learners’ Communicative Competence - BERRAIH, Rachid (My University, 2018)
Classroom interaction is an important aspect in developing the learners’ knowledge and communicative competence, which helps them communicate effectively without obstacles. The purpose of this study is to investigate the crucial role of interaction in enhancing the learners ‘ communicative competence (CC), and its role in providing them with the ability to express their needs.Our research starts with the literature review that sheds the light on the most important concepts that are related to our research. In the practical part, the researcher uses two questionnaires, so that this work contains quantitative and qualitative methods. The teachers’ questionnaire is intended to investigate the teachers’ opinions on the role of interaction in inhancing the learners’CC . The learners questionnaire is intended to investigate whether the learners are able to communicate and make conversation with others through interaction .The results demonstrate that classroom interaction is helpful for the learners to become more competent communicators and they can develop their knowledge . interaction can be used as means to improve CC via the encouragement of collaborative work. Finally this study aims at proposing some suggestions for both teachers and learners on how can interaction develop the learners’CC.
Case study: Third year LMD Students of English at Abdelhamid Ibn Badis University of Mostaganem
Keywords: Communicative competence; Interaction; Communication